1996
DOI: 10.1017/s000186780002735x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic distribution theory for Hoare's selection algorithm

Abstract: We investigate the asymptotic behaviour of the distribution of the number of comparisons needed by a quicksort-style selection algorithm that finds thelth smallest in a set ofnnumbers. Lettingntend to infinity and considering the valuesl =1, ···,nsimultaneously we obtain a limiting stochastic process. This process admits various interpretations: it arises in connection with a representation of real numbers induced by nested random partitions and also in connection with expected path lengths of a random walk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…The equation has a remarkable variety of both theoretical as well as real-world applications. For examples in theoretical probability, see for instance [21,22,24,28,32]. For examples of applications in economics, see for instance [4,34,8,17,26].…”
Section: Discussionmentioning
confidence: 99%
“…The equation has a remarkable variety of both theoretical as well as real-world applications. For examples in theoretical probability, see for instance [21,22,24,28,32]. For examples of applications in economics, see for instance [4,34,8,17,26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, if k < m, then the algorithm recursively operates on the set of keys larger than the pivot and returns the (k − m)-th smallest key from the subset. Although previous studies (e.g., Knuth [11], Mahmoud et al [15], Prodinger [18], Grübel and U. Rösler [7], Lent and Mahmoud [14], Mahmoud and Smythe [16], Devroye [1], Hwang and Tsai [9]) examined Quickselect with regard to key comparisons, this study is the first to analyze the bit complexity of the algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Using martingale methods Regnier [15] showed that (Y n − n log n)/n converges in distribution as n → ∞, Rösler [17] obtained the same result with a completely different and somewhat more constructive method. For Find see Grübel and Rösler [10] and Grübel [8,9], where the convergence in distribution of Z n /n was established for the number Z n of comparisons needed to find a specific quantile such as the median. It is an immediate consequence of these results that there is a concentration of mass phenomenon in the first, but not in the second case: Y n /EY n converges to a fixed value as n → ∞, Z n /EZ n does not.…”
Section: Introduction and Resultsmentioning
confidence: 99%